Trauma exposure and the mediating role of posttraumatic stress on somatic symptoms in civilian war victims - Naser Morina; Ulrich Schnyder; Richard Klaghofer; Julia Müller; Chantal Martin-Soelch (BMC Psychiatry, 2018)
Abstract Background It has been well documented that the exposure to war has a negative effect on the psychological health of civilian. However, little is known on the impact of war exposure on the physical health of the civilian population. In addition, the link between trauma exposure and somatic symptoms remain poorly understood. This cross-sectional study examined levels of somatic symptoms in the aftermath of war, and the mediating role of posttraumatic stress symptoms in the relationship between trauma exposure and somatic symptoms. Methods Civilian war survivors (N = 142) from Kosovo were assessed for potentially traumatic events, posttraumatic stress symptoms, and somatic symptoms. Data were analyzed using mediation analyses. Posttraumatic stress disorder (PTSD) symptoms were categorized based on King’s four factor model (Psychol Assessment. 10: 90-96, 1998). Results Participants reported on average more than 5 types of traumatic exposure. The cut-off indicative for PTSD was exceeded by 26.1% of participants. Symptom levels of PTSD were associated with somatic symptoms. The relationship between trauma exposure and somatic symptoms was partly mediated by the active avoidance and hyperarousal symptom clusters of PTSD. Conclusion Active avoidance and hyperarousal symptoms seem to play a key role in traumatized people suffering from somatic symptoms.